The Regulation of Cybercrime in International Law: Discussing the Legal Frameworks and Challenges in Regulating Cybercrime - Muhammad Umar Asghar; Muhammad Hassan Javed; Sumia Azhar (Indus Journal of Social Sciences, 2025)
The rapid expansion of technology has led to an increase in cybercrime, posing significant challenges for international legal frameworks. The regulation of cybercrime in international law requires a comprehensive and coordinated approach to address the complexities of transnational cyber threats. This paper explores the existing legal frameworks aimed at regulating cybercrime, including the Budapest Convention on Cybercrime, and examines the efforts of various international organizations such as the United Nations and the European Union in combating cybercriminal activities. It discusses the evolving nature of cybercrimes, which range from hacking and identity theft to cyberterrorism and online fraud, and the difficulties in ensuring the effective enforcement of laws across borders. The paper further analyzes the challenges in balancing cybersecurity with individual rights and privacy concerns, as well as the limitations posed by differing national laws and political interests. Additionally, it highlights the need for greater international cooperation and the establishment of universal standards for cybercrime prevention and prosecution. This research aims to provide a critical assessment of current international efforts to regulate cybercrime and suggests potential avenues for strengthening the global legal framework in the fight against cybercrime.